Where to in the Next Ten Years of Health Informatics Education? - Moehr, J. R. (Methods of Information in Medicine, 2006)
Objectives: To explore whether education in health/ medical informaticsa should continue to evolve along the lines pursued since the early seventies, or whether a change is advisable.Methods: Roots and key resulting characteristics for European and US American approaches HI education are identified. In Europe holistic approaches based on a synthesis of medicine and informatics (= computer science) with programs ranging from vocational training through university programs to doctoral and postdoctoral programs were characteristic. The US American approaches emphasized the higher levels of education and a diverse selection of specialized subjects. Changes in health and health informatics are summarized.Results: Two types of changes are identified: high-tech applications arising at the interface of imaging, robotics, and the -omics (genomics, proteomics, metabolomics), and invasive applications centering on consumer health informatics and a move from curative to prospective health care.Conclusions: It is proposed that curative medicine is adequately served by current educational approaches, but that the move towards prospective health care requires a move towards education and change management for health professionals and health informatics professionals.
Keywords: Medical informatics; education; prospective medicine; historical aspects